Vitamin D suppresses inflammatory responses in insulin resistance - Rona Kartika; Heri Wibowo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Vitamin D has been known as a vitamin for bone health and mineral homeostasis. However, since the discovery of vitamin D receptor (VDR) in various types of cell, that statement has changed. Immune cells are known to express VDR and enzyme 1α-hydroxylase that could convert vitamin D into its active form, 1.25 dihydroxyvitamin D. In immune cells, vitamin D works as an immunomodulator which affects various levels of immune response. The net effects of vitamin D are increasing mucosal immunity, but dampening the adaptive immune system. Vitamin D deficiency is commonly found in people with diabetes mellitus (DM) and obesity. It is also associated with increased insulin resistance and poor glucose control. This review will explain how vitamin D as immunomodulator dampens insulin resistance. In immune cells from subjects with insulin resistance, administration of vitamin D could reduce the expression of pro-inflammatory cytokines through the NF-κB and MAPK pathways, thus the levels of pro-inflammatory cytokines such as TNFα, IL-1β, and IL-6 are decreased. The same thing happens in preadipocytes and mature adipocytes cells. In these cells, vitamin D suppresses the expression of pro-inflammatory mediators such as IL-6 and MCP-1. Although in the invitro studies, the administration of vitamin D showed a promising effect in modulating the immune system, the clinical effect of vitamin D supplementation in reducing insulin resistance in individuals with type 2 DM (T2DM) and prediabetes is still inconclusive